PERLINDUNGAN HUKUM BAGI PEKERJA RUMAH TANGGA - Rini Rejeki Susilowati (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2018)
The torture that resulted in the death of the Helper / Domestic Worker (PRT) is a crime against humanity that can not be tolerated anymore, such a condition indicates that Domestic Helper has lost Autonomy and Ownership of him can even be caught in the status of a "slave" is the most vulnerable marginal group to get acts of violence from employers ILO Convention No. 189 on the proper work of domestic servants is a legal protection for domestic workers worldwide, but the existence of ILO Convention 189 does not necessarily concretely as a legal umbrella before it is ratified through the formal legal system in Indonesia, until now Law no. 13 of 2003 on employment does not explicitly recommend about domestic workers, especially concerning the aspect of legal protection as long as the need to realize the protection of Domestic Workers.